Selection of an internal standard to determine mass concentration of uranium in human urine by inductively coupled plasma mass-spectrometry - V.V. Kolbin; M.T. Dyuisembaeva; N.Zh. Mukhamediyarov; A.Zh. Tashekova; G.M. Yesilkanov; Ye.Z. Shakenov; A.Ye. Temirzhanova (Eurasian Journal of Physics and Functional Materials, 2023)
The paper presents experimental studies on the choice of an internal standard in order to correction the matrix effect that occurs when determining uranium in human urine by inductively coupled plasma mass spectrometry. Monoelemental standard solutions of Sc-45, Rh-103, In-115, Ir-193, Th-232 were used as internal standards. The levels of the decrease in the sensitivity of analytical signals of internal standards and uranium spikes under the influence of the matrix effect were determined. The ratio of the measured concentration of internal standards in the background solution of 5% nitric acid and in the matrix of the urine simulator was found compared to uranium. Based on this, empirical coefficients were calculated that characterize the difference in the matrix influence on analytical signals of the internal standard and uranium signals. Adjustment applied was verified according to the internal standard using calculated empirical coefficients and measured values of analytical signals of the internal standard in samples and in the background solution. Iridium was identified as the most suitable of the elements listed as an internal standard according to various criteria. Based on experimental results, a procedure was developed for measuring uranium in urine using iridium as an internal standard.